2010
DOI: 10.1111/j.1751-2980.2010.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Model for end‐stage liver disease combined with serum prealbumin to predict the prognosis of patients with decompensated liver cirrhosis

Abstract: MELD score ≤ 18 combined with PA ≥ 70 mg/L could predict the 6-month and 1-year prognosis of patients with decompensated liver cirrhosis, and was superior to that of MELD score alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 15 publications
2
19
0
Order By: Relevance
“…In one study, comparing these models, UKELD and updated MELD were poor in predicting mortality compared to other 4 models. 132 Other factors shown to improve the MELD accuracy are HVPG, 133 von Willebrand factor level at a cut-off level of 315%, 134 persistent CRP levels of $29 mg/L, 135 prealbumin levels of >69 mg/L, 136 apoptosis marker CK-18. 137 Refinements to improve the accuracy of MELD would continue and until we find a better score, livers could continue to be allocated using the current MELD based system.…”
Section: Other Suggested Modificationsmentioning
confidence: 99%
“…In one study, comparing these models, UKELD and updated MELD were poor in predicting mortality compared to other 4 models. 132 Other factors shown to improve the MELD accuracy are HVPG, 133 von Willebrand factor level at a cut-off level of 315%, 134 persistent CRP levels of $29 mg/L, 135 prealbumin levels of >69 mg/L, 136 apoptosis marker CK-18. 137 Refinements to improve the accuracy of MELD would continue and until we find a better score, livers could continue to be allocated using the current MELD based system.…”
Section: Other Suggested Modificationsmentioning
confidence: 99%
“…[11] AUC of MELD-Na of this study was found to be 0.70, which was relatively lower than that of other studies, of 0.85 to 0.92. [13,16,17] However, according the suggestion of Muller et al, [23] its diagnostic performance ranged from good-excellent. It would be attributable to its significantly longer follow-up period, of 14 years, than other studies of which follow-up periods were up to 20 months, and the relatively lower AUC of this study might be because it included data from even cases censored during the follow-up period in order to reduce bias in its results.…”
Section: Discussionmentioning
confidence: 99%
“…[12,13] Studies on the prognosis of patients with cirrhosis have been mostly focused on terminal cases and anticipation of short-term mortality, and most of them highlight the analysis of prognosis of patients with cirrhosis rather than classification of patients considering the level of severity. [14][15][16][17][18][19] Moreover, the analysis of prognostic factors for mortality of patients should include not only disease-related factors, but also personal and social factors. Such analysis could provide a comprehensive and systematic understanding of patients diagnosed with cirrhotic complications.…”
Section: Introductionmentioning
confidence: 99%
“…[41] Prealbumin is the earliest serum protein that is altered during conditions of acute malnutrition and is most sensitive toward normalization following nutritional supplementation. Prealbumin presents quite a small body reserve and a short half-life (of approximately 2 days).…”
Section: Discussionmentioning
confidence: 99%